Clinical risk factors and outcomes of massive ascites accumulation after discontinuation of peritoneal dialysis. Issue 1 (1st January 2020) - Chang, Ming-Shan; Chen, Nai-Ching; Hsu, Chih-Yang; Huang, Chien-Wei; Lee, Po-Tsang; Chou, Kang-Ju; Fang, Hua-Chang; Chen, Chien-Liang
Abstract: Background: Encapsulating peritoneal sclerosis (EPS) is a serious complication of peritoneal dialysis (PD), with high morbidity and mortality that requires an early diagnosis for effective treatment. PD withdrawal and bacterial peritonitis are important triggers for the onset of EPS. However, few studies have focused on cases of PD withdrawal without a clinical diagnosis of peritonitis, cirrhosis, or carcinomatosis. We aimed to compare the clinical characteristics and computed tomography (CT) images of patients with or without ascites in such situations and assess clinical outcomes in terms of mortality. Methods: Our retrospective review included 78 patients who withdraw PD between January 2000 and December 2017. Results: Ten patients had ascites, and 68 did not have a significant intra-abdominal collection. The ascites group had a significantly longer PD duration (months; 134.41 [range, 35.43–181.80] vs. 32.42 [733–183.47], p  < 0.001) and higher peritoneal membrane transport status based on the dialysate-to-plasma ratios of creatinine (0.78 ± 0.08 vs. 0.68 ± 0.11, p  = 0.009) and glucose (0.27 ± 0.07 vs. 0.636 ± 0.08, p  = 0.001) than the control group. CT parameters, including peritoneal calcification, thickness, bowel tethering, or bowel dilatation, were not all present in each patient with ascites and EPS. During the 12-month study period, the ascites group had a higher risk for developing EPS (70% vs. 0%, p  < 0.001) and a higher 12-month all-cause mortality (30% vs. 0%, p  = 0.002). Conclusions: Ascites accumulation was not rare after PD discontinuation. A longer PD duration and high peritoneal membrane transport status could predict subsequent ascites accumulation. Furthermore, patients with ascites were at a higher risk of EPS.